Membrane potential and dynamics in a ternary lipid mixture: insights from molecular dynamics simulations. Issue 23 (30th May 2018) - Lin, Xubo; Nair, Vinay; Zhou, Yong; Gorfe, Alemayehu A.
Abstract : Transmembrane potential modulates the structure and dynamics of lipid head-groups and acyl chains. Abstract : Transmembrane potential ( V m ) plays critical roles in cell signaling and other functions. However, the impact of V m on the structure and dynamics of membrane lipids and proteins, which are critical for the regulation of signaling, is still an open question. All-atom molecular dynamics (MD) simulation is emerging as a useful technique to address this issue. Previous atomistic MD simulations of pure or binary model membranes indicated that both ion imbalance and electric field can be used to generate V m, but both approaches failed to yield structural changes in lipids with statistical significance. We hypothesized that a possible reason for this could be oversimplified membrane composition or limited sampling. In this work, we tested if and how V m modulates the structure and dynamics of lipids in a physiologically relevant model membrane. Using a detailed side-by-side comparison, we first show that while both ion imbalance and electric field generate V m in our complex membranes, only the latter could produce physiologically relevant V m . We further show that double bonds in lipid acyl chains have a relatively large sensitivity to V m . A single-bilayer model with an electric field showed the highest sensitivity in simulations under the isothermal–isobaric ( NPT ) ensemble, reproducing expected responses of head-group dipoles to V m and suggesting that this approach may be more suitable for studying the structural effects of V m . Our findings also shed light on the relationship between the macroscopic V m and its atomic-level underpinnings.